TINJAUAN TENTANG PERILAKU MENYIMPANG REMAJA DI KELURAHAN TITI RANTAI KECAMATAN MEDAN BARU KOTA MEDAN - JULIANTI SIAGIAN (Welfare StatE, 2013)
A deviant behavior if the behavior is said to be contrary to the norms that exist in the community. Likewise with adolescent deviant behavior, deviant raised not only because such behavior is against the law, but included in it against the values ​​and norms that exist in society. This study aims to determine what factors encourage teenagers deviating behavior in the Village District Titi Chain New Medan. Type of research is descriptive, where the population were 30 adolescents, 21 of whom are boys and 9 girls. The entire population in the study was taken data. The age limit of the respondents in the study was 11 years and 24 years. Data analysis instrument used was a questionnaire, interviews, and tabulation of data contained in a single table and comes with a description of the observation. Based on the analysis of data from the study showed that there are two factors that promote adolescent deviant behavior that includes internal factors: genes, talent, intelligence, as well as external factors include: family, mass media/print, socio-economic conditions, playmate (associate), and the use of leisure time. Keywords: Behavior, Adolescent, and Social Issues